The new normal and its impact on society: perspectives from ASEAN and the European Union - Nurliana Kamaruddin; Aida Idris; Fernandez, Kevin (Palgrave Pivot, 2024)
"This book focuses on the socio-cultural changes and issues experienced in ASEAN and the European Union in the post-pandemic world. In doing so, chapters discuss the social impact of specific themes such as changing work ethics, migration, and cyber security, which have shifted the cultural and economic landscapes of Southeast Asia and Europe. The book will be useful for policymakers, journalists, students, and those interested in discussions of regionalism, and the effects of Covid-19 on social policies ranging from the individual, domestic laws, to national and supranational policies." --